Stimulation of colonic motility by oral PEG electrolyte bowel preparation assessed by MRI: comparison of split vs single dose. Issue 10 (24th July 2014) - Marciani, L.; Garsed, K. C.; Hoad, C. L.; Fields, A.; Fordham, I.; Pritchard, S. E.; Placidi, E.; Murray, K.; Chaddock, G.; Costigan, C.; Lam, C.; Jalanka‐Tuovinen, J.; et al.
Abstract Background Most methods of assessing colonic motility are poorly acceptable to patients. Magnetic resonance imaging (MRI) can monitor gastrointestinal motility and fluid distributions. We predicted that a dose of oral polyethylene glycol (PEG) and electrolyte solution would increase ileo‐colonic inflow and stimulate colonic motility. We aimed to investigate the colonic response to distension by oral PEG electrolyte in healthy volunteers (HVs) and to evaluate the effect of single 2 L vs split (2 × 1 L) dosing. Methods Twelve HVs received a split dose (1 L the evening before and 1 L on the study day) and another 12 HVs a single dose (2 L on the main study day) of PEG electrolyte. They underwent MRI scans, completed symptom questionnaires, and provided stool samples. Outcomes included small bowel water content, ascending colon motility index, and regional colonic volumes. Key Results Small bowel water content increased fourfold from baseline after ingesting both split (p = 0.0010) and single dose (p = 0.0005). The total colonic volume increase from baseline was smaller for the split dose at 35 ± 8% than for the single dose at 102 ± 27%, p = 0.0332. The ascending colon motility index after treatment was twofold higher for the single dose group (p = 0.0103). Conclusions & Inferences Ingestion of 1 and 2 L PEG electrolyte solution caused a rapid increase in the small bowel and colonic volumes and a robust rise in colonic motility. The increase in both volumes and motility was dose dependent. Such a challenge, being well‐tolerated, could be a useful way of assessing colonic motility in future studies.